Oestrus ovis larval infestation among sheep and goats of Green Mountain areas in Libya (Journal of Advanced Veterinary and Animal Research, 2015)
Heads of sheep (n=180) and goats (n=120) slaughtered at four regions (Labraq, Shahat, Elbeida, and Masa) of Green Mountain areas in Libya were investigated for the  presence  of  larvae  of  Oestrus  ovis.    The  animals were  divided  into  sex  and  age  groups.  The  heads were cut along longitudinal and sagittal axes, and the larvae (L1, L2, and L3) were collected. The infestation rate  was  significantly  higher    in  sheep  (51.66%; n=93/180) as compared to goats (28.33%; n=34/120). In sheep, the rate was higher during May (100%), while in  goat,  it  was  higher  during  August  (70%).  The incidence of L1 peaked in April (90%) for sheep and October  (100%)  for  goats,  while  L2  reached  to maximum in May for sheep (26.95%) and goats (75%). L3 reached to peak in February (50%)  for sheep, and June (25%) for goats. Mean intensity of larval burden was  higher  in  sheep  than  goat,  reaching  to  peak  in June  (9.1  larvae/head)  for  sheep  and  March  (3.5 larvae/head)  for  goats.  The  infestation  rate  was significantly higher in males than females. The older animals were mostly affected as compared to younger animals.  Highest  infestation  rate  was  recorded  in Masa  (45.83%),  and  the  lowest  rate  was  found  in Labraq (40.27%). In conclusion, these findings may be used in designing the control strategies of myiasis in Libya.http://dx.doi.org/10.5455/javar.2015.b105